Gyrokinetic investigations of the electromagnetic geodesic acoustic mode. (1st September 2022) - Xie, Baoyi; Ye, Lei; Chen, Yang; Zhao, Pengfei; Guo, Wenfeng; Xiang, Nong
Abstract: The linear characteristics of the electromagnetic geodesic acoustic mode (GAM) are investigated numerically with the gyrokinetic code GEM. The results indicate that the electromagnetic effect has little influence on the frequency and damping rate of the GAM. The results also show that both m = 1 and m = 2 poloidal magnetic components of the GAM exist, and the m = 1 magnetic component has comparable sine and cosine components, while the m = 2 magnetic component is dominated by the sine component, where m is the poloidal mode number. In addition, the amplitudes of various magnetic components increase with respect to the ratio of plasma pressure to magnetic pressure β and safety factor q . Most importantly, the amplitude of the m = 1 magnetic component is comparable to, or even slightly larger than, that of the m = 2 magnetic component. It is also found that the trapped electron effect may be important for the magnetic components. Furthermore, the various magnetic components are compared with the previous analytical results and some discussions are given.